Recent incidence of congenital heart disease in neonatal care unit of secondary medical center: a single center study - Seon Young Cho; Jin-Hee Oh; Jung Hyun Lee; Jae Young Lee; Soon Ju Lee; Ji Whan Han; Dae Kyun Koh; Chang Kyu Oh (Korean Pediatric Society, 2012)
PurposeWith feasibility in the diagnoses of congenital heart disease (CHD) in the antenatal period, we suspect changes have occurred in its incidence. No data have been reported about the current incidence of simple forms of CHD in Korea. We have attempted to assess the recent incidence and characteristics of CHD in the neonatal care unit of a secondary referral medical center.MethodsMedical records of 497 neonatal care unit patients who underwent echocardiography in the past 5 years were reviewed. Pre-term infants with patent ductus arteriosus and other transient, minimal lesions were excluded from this study.ResultsAlthough the number of inpatients remained stable, the incidence of simple forms of CHD showed a gradual decrease over the 5-year study period; a markedly low incidence of complex forms was seen as well. CHD was observed in 3.7% full-term and 6.8% pre-term infants. CHD was observed in 152 infants weighing >2,500 g (3.5% of corresponding birth weight infants); 65 weighing 1,000 to 2,500 g (9.3%); and 6 weighing <1,000 g (8.0%). The incidence of CHD was higher in the pre-term group and the low birth weight group than in each corresponding subgroup (P<0.001); however, the incidence of complex CHD in full-term neonates was high. The number of patients with extracardiac structural anomalies has also shown a gradual decrease every year for the past 5 years.ConclusionFindings from our study suggest that the recent incidence and disease pattern of CHD might have changed for both complex and simple forms of CHD in Korea.